Durability characteristics of steel fibre reinforced geopolymer concrete. (15th September 2015) - Ganesan, N.; Abraham, Ruby; Deepa Raj, S.
Highlights: Studied the durability characteristics of geopolymer concrete (GPC). Studied the effect of fibre addition on the durability characteristics of GPC. Compared the durability characteristics of GPC with conventional concrete of same grade (CC). Abstract: Escalation in the cost of repair and rehabilitation of concrete structures which develop distress much earlier than the design service life has turned the focus on the durability aspect of concrete. This paper presents the result of an experimental study conducted to evaluate the durability characteristics of plain and fibre reinforced geopolymer concrete and its comparison with Portland cement based conventional concrete. The durability parameters considered in this study include water absorption, abrasion resistance, resistance to chemical attack, effect of alternate wetting and drying and resistance against chloride ions. Test results revealed that plain and fibre reinforced geopolymer concrete possesses superior durability characteristics than conventional concrete of the same grade with respect to most of the durability parameters.